Pengaruh Harga Pokok Produksi Terhadap Penetapan Harga Jual Produk Kopi Janji Jiwa - Tita Naswa Ayu Bintoro; Ciska Silvi Oktavia; Supiah Ratnasari; Muhammad Syahwildan (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Product selling price determination is one of the crucial strategic decisions for any company, especially amidst fierce market competition. One of the main elements that significantly influences product selling price determination is the cost of goods sold (COGS). This research aims to analyze the influence of COGS on product selling price determination at Kopi Janji Jiwa outlets. The research method used is a case study with a quantitative approach, analyzing production cost data and coffee product selling prices. The research population is sales transaction data and production costs of Kopi Janji Jiwa, with samples taken from a specific period. Data analysis techniques involve COGS calculation and profit margin analysis. The results show that increased efficiency in COGS management can help companies maintain a competitive price structure without sacrificing product quality. This finding provides an in- depth understanding of how COGS serves as the basis for pricing, influencing profitability and business competitiveness. The implication of this research is the importance of effective cost management to achieve optimal pricing objectives.